Eksistensi Ma’had Al-Jami’ah Dalam Penguatan Moderasi Beragama Pada Era Revolusi Industri 4.0 - Muhammad Mufid; Ahmad Tabi'in (Institut Agama Islam Negeri Bengkulu, 2021)
Abstract: The Existence of Ma’had al-Jami’ah in Strengthening Religious Moderation in the Era Industrial Revolution 4.0The industrial revolution gave rise to digitalization, offering freedom of expression, triggering exclusive religious doctrinal content to develop and target students, on the other hand, the input of new students has various educational backgrounds, especially knowledge of Islamic sciences. Ma'had al-jami'ah is present as a form of institutionalizing the transmission of the Islamic boarding school's scientific tradition and also strengthens the paradigm of Islamic scientific building. For this reason, the purpose of this study is to reveal the movement of Ma'had al-Jami'ah in strengthening religious moderation in the era of the industrial revolution 4.0. This study uses a qualitative method with an analytical descriptive approach, which provides an overview of the object under study, then focuses on the problem and then processed and analyzed to draw conclusions. The results of the study show that (1) the joint commitment of all academics to synergize in mainstreaming religious moderation through the ma'had al-jami'ah program, (2) Integration of the Ma'had al-Jamiah program with Islamic scientific study programs as a support for qualification achievement. graduates with studies on deradicalization of religious understanding through programs to strengthen religious moderation, 3) Ma'had al-Jami'ah connects with other science tools in a multidimensional era in teaching the study of Islamic sciences in the form of study conten or moderate digital-based narratives.Abstrak: Eksistensi Ma’had al-Jami’ah dalam Penguatan Moderasi Beragama di Era Revolusi Industri 4.0Revolusi industri memunculkan digitalisasi menawarkan kebebasan berekspresi memicu konten doktrinisasi keagamaan ekslusif berkembang dan menyasar kepada kalangan mahasiswa, disisi yang lain input mahasiswa baru memiliki beragam latarbelakang pendidikan khususnya pengetahuan ilmu-ilmu keislaman. Ma’had al-jami’ah hadir sebagai bentuk pelembagaan transmisi tradisi keilmuan pesantren dan juga menguatkan paradigma bangunan keilmuan keislaman. Untuk itu tujuan penelitian ini adalah mengungkap gerak Ma’had al-Jami’ah dalam penguatan moderasi beragama di era revolusi industry 4.0. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif analitik yakni memberikan gambaran terhadap objek yang diteliti selanjutya memusatkan permasalahan dan kemudian diolah dianalisis untuk diambil kesimpulan. Hasil penelitian menunjukkan bahwa yaitu (1) Komitmen bersama semua civitas akademik untuk bersinergi mangarusutamakan moderasi beragama melalui program ma’had al-jami’ah, (2) Integrasi program Ma’had al-Jamiah dengan mata kuliah keprodian keilmuan keislaman sebagai penunjang capaian kualifikasi lulusan dengan muatan kajian deradikalisasi pemahaman keagaman melalui program penguatan moderasi beragama, 3) Ma’had al-Jami’ah mengkoneksikan dengan perangkat ilmu lainya di era multidimensi dalam pengajaran kajian ilmu-ilmu keislaman berbentuk konten kajian atau narasi moderat berbasis digital.